Oceanographic Data of the 33rd Japanese Antarctic Research Expedition from November 1991 to March 1992 - タナカ, カズト; ノグチ, ケンイチ; Tanaka, Kazuto; Noguchi, Ken-ichi (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper